2019
DOI: 10.1007/s00038-019-01303-3
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of domestic violence in Saudi Arabia: a systematic review

Abstract: Objectives The aim of this study is to review the prevalence, risk factors, and outcomes of domestic violence (DV) in Saudi Arabia. Methods Systematic review utilizing PRISMA guidelines conducted on articles focusing on research related to the epidemiology of domestic violence in Saudi Arabia between 2009 and 2017 were identified through electronic databases (PubMed and Embase) and supplemented by cross-referencing and local journal searches. Results Eleven studies were conducted in six cities (Riyadh, Jeddah,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…In Saudi Arabia, I can say during the previous decade, the DVA prevalence of DVA has increased from 32% to 80.7%. 13 This study indicated a similar lifetime prevalence rate, comparing the prevalence of this study with other local studies and using the Arabic version of the NORAQ as an assessment tool. Two studies were conducted in the same city, but with different study settings.…”
Section: Discussionsupporting
confidence: 72%
“…In Saudi Arabia, I can say during the previous decade, the DVA prevalence of DVA has increased from 32% to 80.7%. 13 This study indicated a similar lifetime prevalence rate, comparing the prevalence of this study with other local studies and using the Arabic version of the NORAQ as an assessment tool. Two studies were conducted in the same city, but with different study settings.…”
Section: Discussionsupporting
confidence: 72%
“…Emotional abuse was the most prevalent type, followed by physical abuse. In confirmation to these results, women's exposure to emotional abuse has been increasingly recognized as a form of FV in Saudi community (Afifi 2011;Alquaiz et al 2017;Alzahrani et al 2016;Barnawi 2016;Fageeh 2014;Kazzaz et al 2019).…”
Section: Discussionmentioning
confidence: 65%
“…Several Saudi studies, using either WHO multicountry assessment tool or predesigned questionnaire, found that the life time prevalence of domestic abuse/intimate partner violence was in range of 32% to 80.7% (Al Dosary 2016; Kazzaz et al 2019;Tashkandi 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the COVID-19 pandemic, studies in Saudi Arabia indicated a high prevalence of domestic violence and abuse [ 13 , 18 , 19 , 22 , 23 ]. After the pandemic containment measures were implemented, studies reported that the rates were increasing in most countries and communities, mandating additional measures to control and report domestic violence [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%